ANALISIS TINDAK TUTUR KOMISIF PADA DEBAT PUBLIK CALON BUPATI DAN WAKIL BUPATI KABUPATEN POSO TAHUN 2024 - Stevionika Boso; Ida Nuraeni; Asrianti; Juniati; Arum Pujining Tyas (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
This study employs a descriptive qualitative approach to describe the forms of commissive speech acts in the public debate of the 2024 regent and deputy regent candidates of Poso Regency. Data were collected through non-participant observation, listening, and note-taking techniques on the candidates’ utterances across three debate sessions broadcast through official media channels. The data were analyzed using the interactive model proposed by Miles and Huberman. The findings reveal 59 commissive utterances, consisting of 56 promises (marked by expressions such as will, we will maintain, menjamin guarantee, we will actualiz, we will expand, we will establish, we will implement, we aspire, dedicated, and resolute, the remaining utterances consist of 2 instances of commissive offering, marked by offering, and 1 instance of commissive refusing, marked by dissent. The study shows that commissive speech acts are not only used to deliver political programs but also to build public trust through issues of unity, religious moderation, welfare, and regional development. The novelty of this research lies in its examination of commissive speech acts in local political debates within a post-conflict society context, which has been rarely discussed in previous studies. The results contribute to the development of pragmatics in political communication and demonstrate that commissive speech acts function as a linguistic strategy used by candidates to express political commitments and build public trust in public debates.